Comparative analysis of the environmental impacts of a Pelamis wave energy device with existing off shore developments and installations - Quinn, Eoghan (The University of Edinburgh, 2011)
Scotland is currently at the forefront of development and expansion of wave energy, especially with recent renewable energy targets. Research and development has increased greatly off the Scottish coastline. Various adjectives can be used to describe wave energy’s creative potential in helping to achieve Scotland’s energy goals. Put simply however the production of wave energy appears to have all the ingredients for success; it is benign, the visual impacts minimal and its energy is reliable, therefore looking to the open seas as a source for sustainable energy to help reduce our carbon emissions has been widely supported. However due to the youth of the industry various marine environmental implications are unknown due to the lack of available data. The following study provides a comparative analysis of the environmental impacts of a wave energy device with existing off shore developments and installations. The study is undertaken in a two-tier process by creating a comparison between research data, interviews and a case study. The adaption of these existing industries allows the study draw its very own conclusion that there is a level of significant environmental harm associated with renewable wave energy particularly concerning Electromagnetic Frequency Cables, Mooring Systems and Noise. The results of this study highlight the need for further research to be undertaken. More stringent environmental impact assessment is required to close the data gap concerning wave energy deployment. The safety of the environment must be guided by appropriate regulations ensuring an effective monitoring programme is in place. This study strongly recommends undertaking further examination relating to the identified environmental impacts, by using the findings within in this paper as a stepping-stone to do so.
A comparative analysis of the environmental impacts of a Pelamis wave energy device with existing off shore developments and installations
Keywords: Wave Energy; Environmental Impact; Pelamis; EMF; Noise; Scotland; MSc Environment & Development